Learning alliances, corporate entrepreneurship and business performance: is there really a linkage?. (28th January 2010) - Haase, Heiko; Franco, Mario
In this study, we investigate how learning alliances affect corporate entrepreneurship. Then, we also analyse the influence of both learning alliances and corporate entrepreneurship on business performance. In order to achieve this objective, we adopt a quantitative research approach in a cross-sectional study of 80 Portuguese small and medium-sized enterprises. For the influence of learning alliances on business performance, the impact of knowledge acquisition and absorptive capacity is mixed. When including corporate entrepreneurship, proactiveness is the decisive variable in all performance measures. Taken together, we must question that strategic learning alliances per se create value in corporate entrepreneurship and performance. In addition, we conclude that the regional economic environment matters. Several implications are presented.